Il cavallo vittorioso nelle gemme del Museo Archeologico di Venezia: Vincas, Non Vincas, Te Amamus - Nardelli, Bruna (Acta Classica Universitatis Scientiarum Debreceniensis, 2024)
In this paper a small group of engraved gems, kept in the glyptic collection of the Archaeological Museum of Venice, is taken into consideration. It is important to underscore their cultural value and our hope is that researches centring on this precious collection might contribute towards the overall progress on glyptic studies. A few intaglios presented here depict victorious horses. In usual iconography horses drawn in profile with a palm branch placed in various positions is the element that permits classification of the gems, into several groups. In the gems under discussion here there are also some intaglios that belong to the group with the image of racing scenes, a very frequent themes in the roman glyptic. Two red jaspers, depicting the chariot race, are very good examples of the elegant simplification of the well-known iconography, the chariot race set in the Circus Maximus: the drawing presents simple and clear shapes with no internal details but with an accuracy displaying the famous cliché of one circus race. The schematic work and the stylistic and technical characteristics of two gems demonstrate the standardisation of the motif and indicate a serial glyptic production during the second century A.D.